Hubungan Antara Insiden Demam Berdarah Dengue (DBD) dan Faktor Sanitasi Lingkungan : Tinjauan Sistematik Review - Juliska, Shelly; Windusari, Yuanita; Novrikasari; Nur Alam Fajar (Poltekkes Kemenkes Kendari, 2023)
Dengue hemorrhagic fever (DHF) is a vector-borne disease caused byflavivirus that causes morbidity and death rates that are still quitehigh globally. This disease is influenced by many factors includingenvironmental factors that have a very close association with theincidence of DHF. Although there have been many previous studies thatanalyzed the relationship of environmental factors to the incidence ofDHF, the results are still inconsistent. This paper aims to analyze therelationship between the incidence of dengue fever and environmentalsanitation factors. The research design used the systematic reviewmethod. Articles are selected using the PRISMA (Preferred ReportingItems for Systematic Reviews and Meta Analysis) method on the googlescholar search engine. The inclusion criteria in this writing arearticles published within the last 5 years, starting from 2019 – 2023with the keyword